White justice in Arizona : Apache murder trials in the nineteenth century - McKanna, Clare V., Jr., 1935-2012 (Texas Tech University Press, 2005)
Though trials in open court suggest impartiality, White Justice in Arizona reveals how, time and again, the judicial system of nineteenth-century Arizona denied Apaches justice. The Captain Jack, Gonshayee, Apache Kid, "Carlisle Kid," and Batdish murder cases offer a sad, compelling commentary on injustice for Native Americans. That these trials all ended in Apache convictions, Clare V. McKanna Jr. argues, proves the unfairness of applying the American legal tradition to a culture that lived by very different social and legal codes. Conquered and forced from their lands by white outsiders, Apaches found their customs and methods of maintaining social control dramatically at odds with a new and completely alien legal system, a system that would not bend to integrate Apache or any other Native American culture. Through case studies of these very different murder trials, White Justice in Arizona probes the federal and state governments' treatment of America's indigenous populations and the cultural clashes that left justice the greatest casualty